Money demand estimation and currency substitution: evidence from Turkey - Zer, İlknur. (Thesis (M.A.)-Bogazici University. Graduate Institute of Social Sciences, 2005., 2005)
In this thesis, I try to represent both the long-run and short-run empirical relationships between the main Turkish macroeconomic series; the M1 money balances, real output and the opportunity costs variables for the period 1987Q1-2003Q3. Throughout the thesis, extended portfolio balance theory is employed and two different scenarios are considered as treating prices I(1) and I(2). Estimation results reveal that the long-run real money balances is a function of the real output, the interest rate spread and the exchange/ depreciation rate as expected. Also, estimated signs are consistent with the theory. Besides, the significant and negative sign of the depreciation rate is also consistent with the existence of currency substitution in Turkey. Based on the long-run model, the short-run model is estimated by simultaneous equation model. Results depict that the relationship between interest rate and money, as well as inflation and money comes into picture not only in the long-run both also in the short-run.|Keywords: Money Demand, Cointegration, Currency Substitution, Error Correction Modeling, Turkey
Keywords: Demand for money.; Cointegration.; Currency substitution.; Econometric models.